2015
DOI: 10.1007/s11604-015-0464-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in radiological imaging frequencies in children before and after the accident at the Fukushima Daiichi Nuclear Power Plant in Fukushima Prefecture, Japan

Abstract: Our results suggest that the number of pediatric radiological examinations decreased after the accident in Fukushima. We should continue to communicate with patients and their families to ensure that they understand the risks and benefits of radiological imaging in order to overcome their concerns about the nuclear disaster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Although previous studies have suggested that there was a reduction in undergoing CT after the accident, these studies were based on aggregated data on a limited region of Fukushima Prefecture, which was near the plant, or in several children's hospitals. 23,24 A second strength was that the present study used regression discontinuity analysis, a quasi-experimental study design. Random variability implies that patients who visited hospitals before and after the accident will be similar on all observed and unobserved baseline characteristics, mimicking a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have suggested that there was a reduction in undergoing CT after the accident, these studies were based on aggregated data on a limited region of Fukushima Prefecture, which was near the plant, or in several children's hospitals. 23,24 A second strength was that the present study used regression discontinuity analysis, a quasi-experimental study design. Random variability implies that patients who visited hospitals before and after the accident will be similar on all observed and unobserved baseline characteristics, mimicking a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
“…CT, X-ray, MRI, US, etc.) at Fukushima Medical University hospital before and after the accident [ 31 ]. The number of outpatients of <10 years of age who underwent CT and X-ray examinations significantly decreased after the accident.…”
Section: Future Prospectsmentioning
confidence: 99%
“…They get relatively higher effective doses because of their higher radiosensitivity. In addition to this, children have a longer lifespan after radiation exposure compared to adults and are also more likely to undergo repeated CT scans throughout their lifetime [ 1 , 6 , 8 ]. The most exposed to ionizing radiation are organs and tissues such as red bone marrow, brain, thyroid gland, etc.…”
Section: Introductionmentioning
confidence: 99%